2020
DOI: 10.1002/smtd.202000349
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Microalgae for Food and Energy Products

Abstract: their size and physiology, and they belong to many different phylogenetic groups that are distinct from plants. [1] Microalgae are the subset of algae that are unicellular and range in size from several to a few hundred micrometers. Most microalgae diversity resides in freshwater or marine systems. Microalgae can grow in extreme environments such as deserts and polar regions, [2] and often show greater efficiency in synthesizing bioproducts compared to land plants. [3] Moreover, algae produce oxygen and seques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 163 publications
(190 reference statements)
0
21
0
Order By: Relevance
“…Microalgae can be cultivated in hot regions at 36 • C and thrive in multiple environments such as seawater, freshwater, and soil [73]. Microalgae cultivation can be conducted in open ponds or close photobioreactors (PBRs) [74,75].…”
Section: Perspectives Of Microalgae Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Microalgae can be cultivated in hot regions at 36 • C and thrive in multiple environments such as seawater, freshwater, and soil [73]. Microalgae cultivation can be conducted in open ponds or close photobioreactors (PBRs) [74,75].…”
Section: Perspectives Of Microalgae Cultivationmentioning
confidence: 99%
“…Open cultivation systems are open ponds and raceway ponds, which provide the best value for the construction cost [137,138] and can be used on a large scale for microalgae cultivation [82]. However, open cultivation systems have several disadvantages: the need for large quantities of water, large land areas, high exposure to pollution, low biomass productivity, loss of algae due to wall-sticking, easy contamination (limiting the system to only a few strains of algae), and difficulty producing long-term algal cultures [73,135,136]. Further, supplying CO 2 to open cultivation systems is one of the main challenges facing microalgae cultivation because of the high cost of CO 2.…”
Section: Microalgae Cultivation Systemsmentioning
confidence: 99%
“…In addition, the flocculation rate also exhibited species dependence with each species beginning to flocculate and arriving at T max at separate times. Flocculation is thought to be governed by the interactions of surface polysaccharides which are positively charged enabling static attraction to the negatively charged microalgae, and as the cell surface composition differs by species (Feofilova 2010), flocculation ability also differs (Ummalyma et al 2017;Liber et al 2020).…”
Section: Flocculationmentioning
confidence: 99%
“…A sustainable and relatively novel food source of nutritional compounds are microalgae. These organisms can produce large amounts of high biological value proteins, long-chain polyunsaturated fatty acids, carotenoids, vitamins, minerals, and phenolic compounds, among others [11][12][13]. Microalgae do not compete for arable land as other food sources do and, depending on their purpose, can even be grown using non-potable water, wastewater, or even salty water.…”
Section: Introductionmentioning
confidence: 99%
“…S. platensis is rich in vitamin B 12 , as it has been reported that it can contain between 1.6 and 3.2 µg of this vitamin per gram of dried mass, which can cover between 25 and 133% of the daily intake recommendations [25]. In the last few years, microalgae biomass has been successfully applied as an additive for food products, giving innovative and healthy alternatives such as vegetarian cookies, pasta, biscuits, mayonnaise, sausages, and gelled desserts [12,26,27]. Some results have shown that the addition of S. platensis at different levels improved some physicochemical and sensorial attributes in wheat pasta such as water absorption capacity, texture, color, as well as antioxidant capacity [28].…”
Section: Introductionmentioning
confidence: 99%